Association of TGF-β Canonical Signaling-Related Core Genes With Aortic Aneurysms and Aortic Dissections - Chen, Jicheng; Chang, Rong (Frontiers in Pharmacology, 2022)
Transforming growth factor-beta (TGF-β) signaling is essential for the maintenance of the normal structure and function of the aorta. It includes SMAD-dependent canonical pathways and noncanonical signaling pathways. Accumulated genetic evidence has shown that TGF-β canonical signaling-related genes have key roles in aortic aneurysms (AAs) and aortic dissections (ADs), and many gene mutations have been identified in patients, such as those for transforming growth factor-beta receptor 1 TGF βR1, TGF βR2, SMAD2, SMAD3, SMAD4, and SMAD6. Aortic specimens from patients with these mutations often show paradoxically enhanced TGF-β signaling. Some hypotheses have been proposed and new AA models in mice have been constructed to reveal new mechanisms, but the role of TGF-β signaling in AAs is controversial. In this review, we focus mainly on the role of canonical signaling-related core genes in diseases of the aorta, as well as recent advances in gene-mutation detection, animal models, and in vitro studies.